Mural as Educational Media at Simpay Asih Kindergarten, Cideres, Majalengka, Jawa Barat - Erwin Ardianto Halim; Sherlywati Sherlywati; Tri Octaviani (Journal of Innovation and Community Engagement, 2021)
Murals as educational media are a means of student development and good social life. Simpay Asih Kindergarten needs other learning media in teaching its students so that murals can be an alternative. Murals also provide motivation in learning. Another impact of a mural is to create a beautiful and positive space. Mural painting is painting in stages. Concepts and sketches are the first stage, then proceed to the preparation of the walls as a medium for painting, and the last stage is the final touch. Teachers and students of Simpay Asih Kindergarten welcomed the implementation of this mural, so that a positive response was obtained. With enthusiasm, the mural can have a positive impact on Simpay Asih Kindergarten students. Keywords: mural; education; kindergarten